2017
DOI: 10.1017/ice.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medicare’s Nonpayment Policy on Surgical Site Infections Following Orthopedic Procedures

Abstract: OBJECTIVE Orthopedic procedures are an important focus in efforts to reduce surgical site infections (SSIs). In 2008, the Centers for Medicare and Medicaid (CMS) stopped reimbursements for additional charges associated with serious hospital-acquired conditions, including SSI following certain orthopedic procedures. We aimed to evaluate the CMS policy's effect on rates of targeted orthopedic SSIs among the Medicare population. DESIGN We examined SSI rates following orthopedic procedures among the Medicare popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…11,13,28 For mediastinitis following CABG, there are a number of possible explanations for why the HAC POA programs did not lead to demonstrable decreases in reported rates of this complication. First, both the Medicare and Medicaid HAC POA programs targeted mediastinitis for non-reimbursement during the index surgical admission for CABG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,28 For mediastinitis following CABG, there are a number of possible explanations for why the HAC POA programs did not lead to demonstrable decreases in reported rates of this complication. First, both the Medicare and Medicaid HAC POA programs targeted mediastinitis for non-reimbursement during the index surgical admission for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…While elimination of additional payment for preventable complications occurring during hospitalization may improve the value of inpatient care by reducing unnecessary spending, the Medicare and Medicaid HAC POA programs have failed to demonstrate any direct influence on reductions in preventable harm 11 13 , 28 For mediastinitis following CABG, there are a number of possible explanations for why the HAC POA programs did not lead to demonstrable decreases in reported rates of this complication. First, both the Medicare and Medicaid HAC POA programs targeted mediastinitis for nonreimbursement during the index surgical admission for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Most were conducted in USA (n=25). [12][13][14]17,19,20,[22][23][24][25][26][27][29][30][31][34][35][36][37]39,40,42,[44][45][46] The remaining studies derived from England (n=2), 11,33 Taiwan (n=2), 16,21 Australia (n=1), 28 Brazil (n=1), 15 Germany (n=1), 18 Israel (n=1), 38 Italy (n=1), 43 New Zealand (n=1), 32 and Republic of Ireland (n=1). 41 Study designs included 21 ITS, 12,14,[17][18][19][20][21]24,[29][30][31][32][33][34]…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…11,36 Interventions were categorised according to the type of intervention, including care bundles, 16,39 care bundles with implementation strategies, [11][12][13]18,21,26,31,43,46 IPC programmes 14,15,17,20,[28][29][30][32][33][34][35][36]38,[40][41][42] and regulations. 19,[22][23][24][25]27,37,44,45 Study outcomes are presented in Error! Reference source not found.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Although it has been more than 10 years since the HAC-POA program was implemented, little is known about whether the program is associated with improved surgical care outcomes. Three studies have examined surgical outcomes associated with the HAC-POA program, but issues with study design, such as the absence of a comparison with the prepolicy period, a control group subject to spillover effects, and a short study period, have limited the evaluation of the HAC-POA program.…”
Section: Introductionmentioning
confidence: 99%